Cross-Border Spillover Effects of the G20 Financial Regulatory Reforms : Results from a Pilot Survey - Briault, Clive; Feyen, Erik; Gonzalez Del Mazo, Ines; Kwok Chung Yee, Brian; Rademacher, Jan; Skamnelos, Ilias (World Bank, Washington, DC, 2018)
In 2009, the G20 embarked on an ambitious financial regulatory reform agenda to address the fault lines that caused the global financial crisis. Although the global benefits are expected to outweigh the overall costs, these reforms could produce cross-border adverse spillover effects to individual emerging markets and developing economies that are not required to implement the reforms themselves, but are affected by their implementation elsewhere. To improve the evidence base on such potential adverse impacts, the World Bank has undertaken qualitative surveys of senior officials at regulatory agencies, local banks, and global banks that are active in seven emerging markets and developing economies. While important caveats prevent the formulation of definitive conclusions, the survey finds that banks and regulators routinely have different perspectives on the impacts. Most banks claim adverse effects on financial products, services, and markets; regulators broadly expect the effects to be positive over the longer term, but some recognize they may be negative during the transition phase. Regulators tend to agree that the (potential for) spillover impacts demand stronger home-host coordination, impose a higher supervisory burden, and require a stronger role for the international community to monitor and evaluate the impacts. The findings also emphasize the need for regulatory consistency within and between jurisdictions to ensure a level playing field. Taken together, more work remains to better understand the nature of these spillover effects, how they shape the provision of commercial financing to meet developmental objectives, and what action can be taken to mitigate any adverse impacts.